Pengaruh Model Pembelajaran Talking Stick Berbantu Media Question Box Terhadap Belajar IPA - Nofita Dewi Pradina; Muhammad Japar; Dhuta S ukmarani (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The purpose of this study was to determine the effect of the Talking Stick model assistedby the Question Box media on the science learning outcomes for fourth grade students at Mojotengah Village, Kedu District, Temnggung Regency. This research is a type of Pre-Experimental Design research, with the One Group Pretest-Posttest Design model. Samples had taken as many as 20 students used as an experimental class. The samplingtechnique used saturated sampling. Data collection used the test method. This test is usedto test the extent to which students experience changes in science learning outcomesbefore and after being treated. The analysis used in this study is the Wilcoxon Signed RankTest with SPSS version 16.0. The results showed the Talking Stick model assisted by theQuestion Box media on the science learning outcomes. Evidence of an increase in studentsscience learning outcomes is a significant difference between the pretest score and theposttest score, the average pretest score 0f 62.45 while the posttest score is 80.3. This issupported by the existence of a hypothesis test conducted with the Wilcoxon Signed RankTest, the Z obtained score -3.729. with Asymp. Sig. (2-tailed) of 0.000 (0.000 < 0.005). basedon the results of the analysis and discussion there was an increase of 17.85 from theaverage results of the preest and posttest. The results of this research can be concludedthat the use of Talking Stick model assisted by the Question Box media has a significanteffect on the science learning outcomeson the theory style and motion